2022
DOI: 10.1007/s11606-021-07351-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Physician Work and Well-being Through Social Network Modeling Using Electronic Health Record Data: a Cohort Study

Abstract: Background Understanding association between factors related to clinical work environment and well-being can inform strategies to improve physicians’ work experience. Objective To model and quantify what drivers of work composition, team structure, and dynamics are associated with well-being. Design Utilizing social network modeling, this cohort study of physicians in an academic health center examined inbasket mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Our second general hypothesis posits that teaming expansiveness exhibits a curvilinear relationship with job satisfaction, in a concave (inverted U) shape, such that greater expansiveness is initially beneficial but becomes harmful at higher levels. Some expansiveness in perception is likely to be beneficial if it helps people distribute burdensome workload or develop fulfilling relationships; for instance, research using electronic health records has found that greater physician well-being is associated with having a higher number of medical assistants within the close support team and a higher share of messages related to ambiguous diagnoses that presumably require more teamwork to solve (Escribe et al, 2022). Yet organizational scholars have also cautioned that large teams tend to bring higher demands and costs for coordinating (Hackman, 1987).…”
Section: Role-oriented Mental Models Of Teamingmentioning
confidence: 99%
“…Our second general hypothesis posits that teaming expansiveness exhibits a curvilinear relationship with job satisfaction, in a concave (inverted U) shape, such that greater expansiveness is initially beneficial but becomes harmful at higher levels. Some expansiveness in perception is likely to be beneficial if it helps people distribute burdensome workload or develop fulfilling relationships; for instance, research using electronic health records has found that greater physician well-being is associated with having a higher number of medical assistants within the close support team and a higher share of messages related to ambiguous diagnoses that presumably require more teamwork to solve (Escribe et al, 2022). Yet organizational scholars have also cautioned that large teams tend to bring higher demands and costs for coordinating (Hackman, 1987).…”
Section: Role-oriented Mental Models Of Teamingmentioning
confidence: 99%
“…Purely relying on self-reported measures, they are subject to inaccuracy of workload measurement and unable to provide unobtrusive burnout prediction [14]. Recently, the quantification of clinician workload based on EHR use has enabled studies to track EHR-based workload measures [5,31], and apply off-the-shelf machine learning to predict burnout based on delicately design summary statistics of clinical activities as features [12,22].…”
Section: Related Workmentioning
confidence: 99%
“…The availability of clinician activity logs, the digital footprint of physicians' EHR-based activities, has enabled studies for tracking EHR-based workload measures [5,31], offering new opportunities for assessing its associations with burnout. More recently, such activity logs have been used to predict burnout using off-the-shelf machine learning models [12,22]. However, as these models are unable to directly process unstructured data, they rely exclusively on feature engineering, using hand-crafted summary statistics of activity logs as features.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, past attempts to disseminate new technologies into healthcare systems have often resulted in unintended consequences, such as an increase in the administrative burden on physicians and clinical teams. [5] Moreover, despite several successful proof of concepts and prototype pilots, the number of large-scale field implementations of AI-enabled software within healthcare systems is still relatively low. [6], [7] As hospitals begin to experiment with generative AI (GAI) tools in clinical settings, it is important to identify known challenges that might stand in the way of achieving better patient care and lower administrative burdens -and, where possible, document practices that can mitigate those challenges.…”
Section: Introductionmentioning
confidence: 99%